First step towards understanding the specific identity of fish muscle parasites of the genus Sarcotaces (Copepoda: Philichthyidae)—New species and first molecular ID in the genus. (August 2022) - Piasecki, Wojciech; Barcikowska, Dominika; Panicz, Remigiusz; Eljasik, Piotr; Kochmański, Paweł
Abstract: Parasitic copepods of the genus Sarcotaces are remarkable. They occur in galls inside skeletal muscles of fishes and it is virtually impossible to overlook them, especially during fish handling and processing. The galls contain an intensively black ink-like substance that may stain fish tissue during filleting. They have a global distribution and until recently, seven nominal species had been described, each from a host representing a different fish family. Females of valid species are quite similar in their morphology, therefore the males are essential for species determination. Even though such a task may be difficult, because of the existing inadequate descriptions that additionally hinder correct identification. The aim of this study was to provide a detailed morphological and molecular characterization of the Sarcotaces specimens found in muscles of the common mora, Mora moro (Risso, 1810), most probably originating from southern Australia. The additional aim was to indicate possible mode and strategy of infection for the parasitic copepods of the genus Sarcotaces . The present paper not only describes and illustrates Sarcotaces izawai sp. nov. but also provides its molecular ID based on the COI gene. In addition to traditional light microscopy studies, Scanning Electron Microscopy (SEM) was also used. Males of Sarcotaces izawai sp. nov. differ from those of its congeners: in the host fish family, in the relative proportions of the caudal rami, and in the setal formula of the antennulae. For the first time in this genus, we described the maxillulae. We also discussed the possible mode and strategy of infection and redefined mesoparasitism. Graphical abstract: Image 1 Highlights: A new species and the first genetic ID of a species representing the genus Sarcotaces and the family Philichthyidae. Discovery of hitherto overlooked maxillule (in the genus). Unprecedented phenotypic variability of the caudal rami and posterior part of the body in males. Infection site and infection strategy explained/hypothesized. Mesoparasitism redefined.